Penggunaan E-Learning Berbasis Media Sosial Edmodo bagi Guru Sekolah Dasar Negeri Mulyorejo I Surabaya - Iriyani, Dwi; Hatip, Ahmad; Anshori, Sodiq (Penerbit STKIP PGRI Bangkalan, 2018)
This article presents the findings of community service program conducted by UPBJJ-UT Surabaya for teachers in fiscal year 2017. This program includes the efforts to improve the quality of education, and public welfare. Based on the analysis with the teacher partner, the community service focuses on âThe training of using social media-based e-learning âedmodoâ on teachers of Sekolah Dasar Negeri Mulyorejo I Surabayaâ This program was held in six months during June-November 2017 and started by some steps such as: planning, preparation, and implementation. The findings of this program can be obtained through the evaluation process, the products, and the participantsâ responses toward the implementation of Edmodo by conducting the satisfaction questionnaire. It can be concluded that the teachers partner are very enthusiastic and interested in participating this training.